The Drama of Language Learning: Using English Literature with a Polish Teenage Youth Theatre - Hill, Trevor (Acta Neophilologica, 2024)
The positive effects of using drama in ELT have long been recognized, however this has often been explored from the context of the classroom. The article retroactively examines the activities of an English language youth theatre club for Polish teenagers as a social event organized in addition to their academic studies of the language. Special attention is paid to the use of classic texts (albeit adapted) by authors such as Shakespeare, and particularly the World War One poetry of Wilfred Owen. The article examines the techniques of using and performing the texts, the importance of gesture and intonation, as well as the necessity to explore cultural and historical aspects of the material. The students’ opinions of the work and the effect on their language learning were submitted in a questionnaire and are presented towards the end of the article.